Characteristics Of Nata De Guava Peels With Variation Of Concentration Guava (Psidium Guajava) Peels And Time Of Fermentations - Gunawan, Ahmad; Karyantina, Merkuria; Mustofa, Akhmad (JITIPARI (Jurnal Ilmiah Teknologi dan Industri Pangan UNISRI), 2021)
Nata is a kind of jelly white or clear chewy jelly, which is generally derived from the fermentation process of coconut water. The fermentation process of nata is assisted by Acetobacter xylinum. These bacteria have chemo-organotrophic properties, which are able to convert the sugar in coconut water into cellulose fiber sheets. Nata is not only made from coconut water. This research uses guava (Psidium guajava) peels extract to replace coconut water. Guava peels contains antioxidant compounds that are much higher than the fruit fraction. This study used factorial RAL, namely the concentration of guava peel extract and the time of the fermentation. The first factor is the ratio of guava peels extract, namely 50 grams / 300 ml, 75 grams / 300 ml and 100 grams / 300 ml. Factor 2 is the time of fermentation, namely 5 days, 10 days and 15 days. Testing for nata de guava peels includes chemical tests (antioxidant activity, total sugar, pH, moisture content, ash and crude fiber content) and organoleptic tests (color and texture). The results of the best treatment formulation of chemical tests on the manufacture of nata de guava peels are the ratio of 100 / 300ml guava extract and 10 days of fermentation, where antioxidant activity is 89.88%, crude fiber is 3.55%, total sugar is 5.636%, ash content is 0.407 %, pH 4 and water content of 82.77%. Organoleptic results were 3.48 texture test and 3.23 color test.